The Labor Market Impacts of Venezuelan Refugees and Migrants in Brazil - Mrittika Shamsuddin; Pablo A. Acosta; Rovane Battaglin Schwengber; Jedediah Fix; Nikolas Pirani (Institute of Labor Economics (IZA), 2022)
As more and more Venezuelans leave their country, fleeing the economic and social crisis, the number of Venezuelans in Brazil has risen steadily since 2016, constituting about 18.6 percent of Brazil's 1.4 million refugee and migrant population as of October 2020. Past research finds that the impacts of forced displacement on the labor market outcomes of host community are mixed and tend to depend on country characteristics. This paper extends the previous literature by exploring the economic impact of Venezuelan influx on Roraima, the state bordering the República Bolivariana de Venezuela at the north and the main gateway of the Venezuelan refugees and migrants entering Brazil, and focusing on the formal sector employment of the host community. Using survey and administrative data and regression discontinuity frameworks, this paper finds that in the short-run, the Venezuelan influx led to an overall increase in unemployment and a decrease in informal sector employment, specially among the female workers in Roraima. Focusing on the host community, the findings suggest that Venezuelan influx led to increase in formal sector employment among the Brazilians, while the effect on both overall and native wages are heterogenous, suggesting distribution impacts and need for gender targeted policies.
Keywords: J21; J31; J61; F22; F15; O15; R23; H20; H50; 330; labor market impacts; Venezuelan refugees and migrants; host community; forced displacement